2012
DOI: 10.1016/j.oooo.2012.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic analysis of 493 cases of salivary gland tumors in a Southern Brazilian population

Abstract: The present data confirm that PA and MEC are the most common benign and malignant SGTs. However, it is important to consider that differences in tumor types may be influenced by whether a tumor derives from a medical or a dental service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

53
138
7
23

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(221 citation statements)
references
References 41 publications
53
138
7
23
Order By: Relevance
“…Lukšić et al [4], Tian et al [10], and Wang et al [17] reported that ME cases are more common in parotid gland. The most common malignant tumor types were ACC and MEC in our series as in the literature [4,[10][11][12][13][14][15][16][17][18][19][20][21][22]. There was a location predilection for certain malignant tumor types but MEC has a similar frequency when parotid and minor gland localizations are compared.…”
Section: Pediatric Groupmentioning
confidence: 52%
See 2 more Smart Citations
“…Lukšić et al [4], Tian et al [10], and Wang et al [17] reported that ME cases are more common in parotid gland. The most common malignant tumor types were ACC and MEC in our series as in the literature [4,[10][11][12][13][14][15][16][17][18][19][20][21][22]. There was a location predilection for certain malignant tumor types but MEC has a similar frequency when parotid and minor gland localizations are compared.…”
Section: Pediatric Groupmentioning
confidence: 52%
“…PA is invariably the most common tumor type among all salivary gland neoplasms with reported rates between 38.4 and 67.8 % [4,[10][11][12][13][14][15][16][17][18][19][20][21][22]. WT is known as the second most common benign salivary gland neoplasm and this tumor almost always originates from parotid gland as in our series.…”
Section: Pediatric Groupmentioning
confidence: 64%
See 1 more Smart Citation
“…Salivary gland tumors (SGTs) consist of a group of heterogeneous lesions with complex clinicopathologic characteristics and distinct biological behavior that correspond to approximately 3% to 10% of the neoplasms of the head and neck region [1][2][3][4][5]. Epidemiological studies have shown geographical differences in the incidence and frequency of histological subtypes of SGTs [1].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown geographical differences in the incidence and frequency of histological subtypes of SGTs [1]. In this retrospective study, hospital records of 244 patients with salivary gland tumors were documented with demographic features and histological diagnosis.…”
Section: Introductionmentioning
confidence: 99%